Carcinoma of the Uterine Cervix in the Kumaon Region: Evaluation of Factors Contributing to Presentation at Advanced Stages (Stages IIB-IVB) - Mohan, Lalit; Arya, Aradhana; Pandey, Kailash Chandra; Pant, Nirdosh Kumar; Revannasiddaiah, Swaroop; Sarangi, Satya Sadhan; Singh, Jyoti (Asian Journal of Medical Research, 2018)
Background: Cervical cancer is the second most common cancer in Indian women, contributing to about fifth part of total cancer incidence. Majority of the cervical cancer cases in India present at advanced stages (Stage II B onwards). The purpose of this study is to analyze and evaluate factors which are contributing to presentation of cancer cervix patients in advanced stages. Subjects and Methods: This observational study recruited new and follows up patients of histologically confirmed diagnosis of cervical cancer visiting in outdoor patient department of Swami Rama Cancer Hospital and Research Institute, Haldwani, India (SRCH & RI) were asked to read and fill questionnaire, inquiring the details of factors which contributed to delayed presentation to seek health services; from 1st April 2017 to 31st March 2018. Of the 221patients were recruited in this study, 6 patients were excluded for ambiguous history and 4 patients for consent withdrawal. Results: Of the 211 patients recruited in study, mean age of presentation was 53 years (SD 11.2), ranging from 30 to 78 years. Financial constrains (71%), lack of awareness for disease (66%), illiteracy (85%), difficult access to health services (46%), taking alternative treatment (30%) and poor family support (18%) were the most important contributing factors for delayed presentation at advanced stages. Lack of awareness that abnormal uterine bleeding could be malignancy, difficult access to health services, alternative treatment, low socioeconomic status, illiteracy and poor transportation services are main contributing factors to presentation of carcinoma cervix in advance stages. Conclusion: Apart from a proper screening programme; difficult access to health services due to remote location of residence in hilly areas, low awareness for cervical cancer, low socioeconomic status and lack of education are important contributory factors for presentation of cervical cancer in advanced stages.